Is Clostridium difficile associated with the '4C' antibiotics? A retrospective observational study in diabetic foot ulcer patients. Issue 5 (6th February 2014) - Collier, A.; McLaren, J.; Godwin, J.; Bal, A.
Summary Aims Clostridium difficile is an anaerobic cytotoxin‐producing bacterium that can cause infectious diarrhoea, pseudomembranous colitis and toxic megacolon. The major risk factors for developing C. difficile infection include recent or current antimicrobial use, diabetes, age over 65, proton pump inhibitor use, immunosuppression and previous infection with C. difficile. Most diabetic foot ulcers are polymicrobial. Methods As a result guidelines advise treatment with broad spectrum antibiotics which include the '4C's' (clindamycin, cephalosporins, co‐amoxiclav and ciprofloxacin) which are associated with a higher risk of C. difficile infection. Retrospective observational data (June 2008 to January 2012) for the diabetes foot ulcers were gathered from the Diabetes/Podiatry Clinic database in NHS Ayrshire and Arran and cross‐matched with the NHS Ayrshire and Arran Microbiology database. There were 111 patients with mean age 59 years (range 24–94 years), 33 type 1 patients, 78 type 2 patients, mean duration of diabetes 16 years (6 months–37 years) and mean HbA1c 67 mmol/mol (54–108 mmol/mol) [8.3% (7.1–12%)]. Results The total number of days antimicrobials prescribed for all patients was 7938 (mean number of antimicrobial days per patient = 71.5 days). There was one case of C. difficile infection of 111 patients giving an incidence of 1.25 cases per 10, 000 patient‐days of antibiotics/1 case per 209 foot ulcers. Conclusions Large doses, numbers and greater duration of antibiotic therapy all result in a greater degree of normal gut flora depletion. It is possible that the alterations in gut flora in diabetic foot ulcer patients protect them from antibiotic‐induced C. difficile overgrowth.